Corak Isyari dalam Tafsir Ruh al-Ma’ani Karya al-Alusi - Anas Mujahiddin (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2022)
This article aims to find out the isyari style contained in this interpretation of Ru>h al-Ma'a>ni> by Imam al-Alu>si. This article also aims to state that this Ru>h al-Ma'a>ni> interpretation is an isya>ri style interpretation. The methodology used in this article is a literature study, by reviewing and analyzing the literature related to the style of Sufi interpretation, the method of Sufi interpretation, and the interpretation of Ru>h al-Ma'a>ni itself. The finding in this article is that this interpretation of Ru>h al-Ma'a>ni> has a Sufi tendency so that this interpretation is classified into the interpretation of the isya>ri style.